Second International Electronic Conference on Medicinal Chemistry (ECMC-2) - Annie Mayence; Jean Jacques Vanden Eynde (MDPI AG, 2017)
The second International Electronic Conference on Medicinal Chemistry, organized and sponsored by the publisher MDPI AG and the Journal Pharmaceuticals, took place in November 2016 on the SciForum website (www.sciforum.net/conference/ecmc-12). More than 150 authors from 22 countries participated in the event. Selected works presented during the scientific meeting are disclosed in this report.